An overview of challenges to eradication of Helicobacter pylori infection and future prospects - Bagirova, M.; Allahverdiyev, A. M.; Abamor, E. S.; Aliyeva, H.; Unal, G.; Tanalp, T. D. (VERDUCI PUBLISHER, 2017)
The eradication of H. pylori infection continues to be a challenge due to the evolution of drug-resistant bacteria, lack of a gold standard diagnostic method, and ineffectiveness of current vaccines. Additionally, there still is no consensus in the literature about the main source of gastric H. pylori infection. The bacterium has also been demonstrated to colonize in dental plaque and the oral cavity. We believe that to develop new approaches for successful eradication of the disease, factors such as the biology of the bacterium, reservoir differentiations, host-bacterium interactions and problems in diagnosis, treatment and vaccination must be comprehensively considered. Therefore, the main goal of this study is to gather all of the literature analysis about the problems in the eradication of the infection, reconsider contradictions about extra-gastric reservoirs of the bacterium, and propose new strategies aimed at disease eradication.
Keywords: H. pylori; Infection; Eradication; Diagnosis; Vaccination; Dental plaque; Oral cavity; GASTRIC EPITHELIAL-CELLS; POLYMERASE-CHAIN-REACTION; PROTON PUMP INHIBITOR; KAPPA-B ACTIVATION; ORAL-CAVITY; TRIPLE THERAPY; HIGH PREVALENCE; MICROCULTURE METHOD; RESCUE THERAPIES; Pharmacology & Pharmacy